Interventions to integrate care for people with serious mental illness and substance use disorders: a systematic scoping review protocol - Lauralie Richard; Amy Richardson; Kathryn Gunter (BMJ Open)
Introduction People with serious mental illness (SMI) and/or substance use disorders (SUDs) have an elevated risk of premature mortality compared with the general population. This has been attributed to higher rates of chronic illness among these individuals, but also to inequities in healthcare access and treatment. Integrated care has the potential to improve the health of people with SMI/SUDs. The aims of this scoping review are to: (1) identify empirical investigations of interventions designed to integrate care for people with SMI/SUDs; (2) describe the underlying theories, models and frameworks of integrated care that informed their development; and (3) determine the degree to which interventions address dimensions of a comprehensive and validated framework of integrated care.Methods and analysis Guidelines for best practice and reporting of scoping reviews will be followed using the framework of Arksey and O’Malley and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses scoping review checklist. An iterative and systematic search of peer-reviewed publications reporting empirical research findings will be conducted. This literature will be identified by searching five databases: Medline (Ovid), PsycINFO, CINAHL, Embase (Ovid) and Scopus. The search will be restricted to articles published between January 2000 and April 2019. Two reviewers will independently screen publications in two successive stages of title and abstract screening, followed by full-text screening of eligible publications. A tabular summary and narrative synthesis will be completed using data extracted from each included study. A framework synthesis will also be conducted, with descriptions of interventions mapped against a theoretical framework of integrated care.Ethics and dissemination This review will identify the extent and nature of empirical investigations evaluating interventions to integrate care for people with SMI/SUDs. Ethical approval was not required. A team of relevant stakeholders, including people with lived experience of mental health conditions, has been established. This team will be engaged throughout the review and will ensure that the findings are widely disseminated. Dissemination will include publication of the review in a peer-reviewed journal. The review protocol has been registered through Open Science Framework and can be accessed at https://osf.io/njkph/